2015
DOI: 10.1002/hed.24096
|View full text |Cite
|
Sign up to set email alerts
|

Convallaria keiskei as a novel therapeutic alternative for salivary gland cancer treatment by targeting myeloid cell leukemia‐1

Abstract: MECK can be used as a safe and efficient therapeutic alternative for the treatment of salivary gland cancer. © 2015 Wiley Periodicals, Inc. Head Neck 38: E761-E770, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
(148 reference statements)
0
4
0
Order By: Relevance
“…For example, steroidal glycosides extracted from C. majalis whole plants had the potential for use as an anti-lung cancer agent [ 13 ]. Convallaria keiskei plants was used in the treatment of salivary gland cancer as an efficient therapeutic alternative [ 14 ]. Although Convallaria species have high medicinal and horticultural values, studies on the phylogenetic relationships and evolution of these Convallaria species are few.…”
Section: Introductionmentioning
confidence: 99%
“…For example, steroidal glycosides extracted from C. majalis whole plants had the potential for use as an anti-lung cancer agent [ 13 ]. Convallaria keiskei plants was used in the treatment of salivary gland cancer as an efficient therapeutic alternative [ 14 ]. Although Convallaria species have high medicinal and horticultural values, studies on the phylogenetic relationships and evolution of these Convallaria species are few.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we excluded the possibility that Mcl-1 expression was regulated at the transcriptional level upon EEPK treatment. Previous studies have reported that translational inhibition of Mcl-1 expression in response to naturally occurring compounds attributes to the induction of G 2 /M cell cycle arrest or apoptosis in several cancer cells, which was involved in the phosphorylation status of translation initiation factors such as eIF4E or eIF4G [ 20 , 21 ]. In the present study, we observed an apparent decrease in the phosphorylated levels of eIF4E, suggesting that the EEPK-induced inhibition of eIF4E phosphorylation contributes to the decrease in Mcl-1 protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic effects of numerous natural product-derived drugs have been evaluated for the management and prevention of many different types of cancer (Aung et al, 2017;Mitra and Dash, 2018). The major advantages of using natural resourcebased products particularly for cancer treatment are as follows: (a) minimal or low adverse effect; (b) their ability to react to many cancer types; (c) comparably easy accessibility; and (d) the mixture of multiple potent anti-tumor components (Lee et al, 2016). Among various natural substances, caffeic acid has been reported to possess anti-inflammatory (Dos Santos and Monte-Alto-Costa, 2013), antioxidant (Sulaiman et al, 2014), and anti-tumor effects (Lin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%